2021
DOI: 10.1002/pc.26101
|View full text |Cite
|
Sign up to set email alerts
|

Study of mechanical, flame, and water stability of phenolic resin / carbon fiber / nanosilica composites

Abstract: Phenolic resin-carbon fiber composites are used in various industries due to their high flame resistance, high strength to weight ratio, and high thermal stability as an insulator. In this study, to expand the applications of this composite in marine structures, phenolic resin-carbon fiber-nanosilica composites were fabricated with eight layers of twill carbon fibers and 0, 1, 2, and 3 wt% of nanosilica then flexural and flame resistance was investigated. To evaluate the stability of the composites in seawater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…[18] Different catalytic methods like acid, base, CrCl 2 , and CrCl 3 catalysts were also explored to study their effect on the synthesis of novolac and resol-typephenol-furfural resin. [12,17,19,20] Less reactivity of the furfural made the synthesis of phenol-furfural resin more complicated than the PF resin synthesis. The correlation between the reaction conditions and the structure and properties of the phenol-furfural resin is not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…[18] Different catalytic methods like acid, base, CrCl 2 , and CrCl 3 catalysts were also explored to study their effect on the synthesis of novolac and resol-typephenol-furfural resin. [12,17,19,20] Less reactivity of the furfural made the synthesis of phenol-furfural resin more complicated than the PF resin synthesis. The correlation between the reaction conditions and the structure and properties of the phenol-furfural resin is not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…Chen [ 4 ] prepared carbon‐quartz fiber reinforced phenolic‐silica aerogel nanocomposite by using the dipping method, and the composites have good thermal ablation and insulation performance in oxyacetylene ablation oxidation flame. Bakhshi [ 15 ] found that nanosilica particles could significantly help increase the flexural strength and flame resistance of phenolic composites. Some researchers investigated the interlaminar mechanical performance to improve composites' ablative performance.…”
Section: Introductionmentioning
confidence: 99%
“…The success of the reinforcing phase always depends on the amount, distribution and dispersion of the nano-particles inside the matrix. [13][14][15][16][17] In this work ZrO 2 , SiC, and MgO nano-particles were selected to be added to a lightweight carbon-phenolic ablator (ρ ~0.3 g/cm 3 ) for their low density, low thermal conductivity, and high melting point. At first, samples of phenolic resin and nano-particles were manufactured in order to understand the influence of the nano-fillers on the mechanical properties of the unreinforced phenolic resin.…”
Section: Introductionmentioning
confidence: 99%
“…The success of the reinforcing phase always depends on the amount, distribution and dispersion of the nano‐particles inside the matrix. [ 13–17 ]…”
Section: Introductionmentioning
confidence: 99%